2007
DOI: 10.1038/sj.jp.7211669
|View full text |Cite
|
Sign up to set email alerts
|

Use of neostigmine to relieve a suspected colonic pseudoobstruction in pregnancy

Abstract: Neostigmine is a treatment option for colonic pseudoobstruction. However, experience in using neostigmine for this indication in pregnant women is limited. We present a case of a woman with an estimated fetal gestational age of 34 weeks presented with what was believed to be a pseudoobstruction and when conservative management failed, neostigmine was administered with no adverse side effects. Ultimately, the patient was found to have a mechanical obstruction and we discuss the challenges in making this diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…The fetus therefore should be monitored continuously, and the obstetric team can proceed immediately to delivery by cesarean if indicated. 11 When neostigmine management fails or is contraindicated, colonic decompression should be done to decrease the risks of ischemia and perforation. Decompression generally is recommended when the colon is dilated more than 12 cm.…”
Section: How Is Ogilvie Syndrome Diagnosed? Does This Change In Pregnmentioning
confidence: 99%
See 1 more Smart Citation
“…The fetus therefore should be monitored continuously, and the obstetric team can proceed immediately to delivery by cesarean if indicated. 11 When neostigmine management fails or is contraindicated, colonic decompression should be done to decrease the risks of ischemia and perforation. Decompression generally is recommended when the colon is dilated more than 12 cm.…”
Section: How Is Ogilvie Syndrome Diagnosed? Does This Change In Pregnmentioning
confidence: 99%
“…The estimated fetal exposure of a lower gastrointestinal series is 2-4 rads; it should be used carefully during pregnancy, especially because various radiographic studies have suggested that 5 rads is the safe upper limit for fetal exposure. 11 There are two critical diseases that present like Ogilvie syndrome: mechanical colonic obstruction and toxic megacolon. Mechanical colonic obstruction may be caused by sigmoid volvulus, tumors, benign stricture, or fecal impaction; toxic megacolon may be caused by infection.…”
Section: How Is Ogilvie Syndrome Diagnosed? Does This Change In Pregnmentioning
confidence: 99%
“…In addition, atropine should be available at the bedside and patients should receive continuous electrocardiographic monitoring with vital sign for 30 minutes. The use of neostigmine in pregnancy has not been well-studied (6). The rate of recurrence of acute colonic pseudo-obstruction after neostigmine ranges from 5 to 33% (7).…”
Section: Correct! 2 Neostigmine An Acetylcholinesterase Inhibitor mentioning
confidence: 99%
“…Sir William Heneage hat das Ogilvie-Syndrom 1948 erstmals bei 2 Patienten beschrieben [6]. Insgesamt werden mehrere kasuistische Fälle des Ogilvie-Syndroms nach Sectio caesarea in der Literatur beschrieben [1,3,8,12,13] Abb. 4 a, b).…”
unclassified
“…Aber auch die Schwangerschaft allgemein [6], ein begleitendes HELLP-Syndrom [7], Mehrlingsschwangerschaften mit einem fetofetalen Transfusionssyndrom [9] und die normale vaginale Entbindung können zu einem Ogilvie-Syndrom führen [10]. Insgesamt werden in der Literatur nur 5 Fälle mit akuter Pseudoobstruktion während der Schwangerschaft berichtet [9,13]. Die meistvertretene Hypothese ist die, dass eine Imbalance im autonomen Nervensystem die Ursache des ACPO ist [2,3,5,9,11].…”
unclassified